Transformasi Pembelajaran IPA di MI melalui Praktikum Sederhana agar Siswa Lebih Aktif - Mohammad Jefri Nabili Nur Faizin; Muhammad Suwignyo Prayogo (Journal of Science and Mathematics Education, 2026)
Low student participation in science learning at Madrasah Ibtidaiyah remains a significant challenge that can affect both the learning process and students’ academic achievement. This study aimed to examine the effectiveness of transforming science instruction through simple practicum activities in enhancing student engagement. A quantitative approach was employed using a pre-experimental one-group pretest-posttest design. The participants were 30 fifth-grade students selected through purposive sampling. Data were collected through observation, questionnaires, interviews, and documentation, and were analyzed using descriptive and inferential statistics. The findings revealed that the implementation of simple practicum activities significantly improved students’ active participation in science learning. Students showed greater willingness to ask questions, express their opinions, collaborate with peers, and participate in hands-on activities. Observational data indicated an increase in the number of students categorized as active and highly active following the intervention. In addition, interview and documentation results demonstrated that students became more enthusiastic, confident, and engaged throughout the learning process. These findings suggest that the transformation of science learning through simple practicum activities is effective in increasing student engagement and fostering a more interactive, contextual, and student-centered learning environment at Madrasah Ibtidaiyah.